PENINGKATAN AKTIFITAS PEMBELAJARAN SEJARAH DI MASA PANDEMI COVID-19 MELALUI MODEL BLENDED LEARNING - SARI FATOLLAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This Best Practice writing aims to describe the increase in history learning activities during the COVID-19 pandemic through the blended learning model. The subjects of this Best Practice writing are XII IPS 3 students at SMA N I Karangrayung semester 1 of the 2021/2022 academic year, totaling 33 students. Best Practice writing uses descriptive method. This writing is motivated by efforts to increase student learning activities, since the issuance of the four ministerial decrees that allow schools to organize limited face-to-face learning using a blended learning model that combines online and face-to-face activities. The implementation of blended learning can improve history learning activities as shown in student learning outcomes. Based on the results of the evaluation before the action, the individual scores of students who finished studying with a score of 70 or more were 15 students or (45.45%) while those who had not finished studying were 18 students or (54.55%) the average score. 62.91 with the highest score of 80 and the lowest score of 45, after using the blended learning model of student activities there was an increase, this can be seen from the achievement results, from 15 students (45.45%) completed to 30 students (90.9 ,%). Meanwhile, those who have not finished have decreased from 18 students (54.56%) to 3 students (09.09%), 5 students (15.15) high, 10 students (30.3%) with sufficient achievement. In addition, students with very low criteria amounted to 3 students (09.09%). The students with low criteria amounted to 4 people (12.12%), and students with very low criteria were 3 people (9.09%), while for very high criteria there were none. very high achievement criteria are 9 people (27.27%), high achievement are 12 people (36.36%), enough are 9 people (27.27%), besides students with low criteria are 3 people (9, 09%), and there are no students with very low criteria. ABSTRAKPenulisan Best Practice ini bertujuan untuk mendeskripsikan peningkatan aktivitas pembelajaran sejarah di masa pandemi covid -19 melalui model pembelajran blended leaning Subyek penulisan Best Practice ini adalah siswa XII IPS 3 di SMA N I Karangrayung semester 1 tahun pelajaran 2021/2022 yang berjumlah 33 siswa. Penulisan Best Practice menggunakan metode deskriptif. Penulisan ini dilatarbelakangi oleh upaya untuk meningkatkan aktivitas belajar siswa, sejak terbitnya SKB empat menteri yang memperbolehkan sekolah untuk menyelenggarakan Pembelajaran tatap muka terbatas menggunakan model blended learning mengombinasikan kegiatan daring dan tatap muka. Implemantasi pembelajran blended learning dapat meningkatkan aktifitas belajar sejarah sebagaimana ditunjukkan dalam hasil belajar peserta didik. Berdasarkan hasil evaluasi sebelum tindakan, nilai secara indivdu peserta didik yang tuntas belajar dengan nilai 70 atau lebih ada 15 siswa atau sebesar (45,45 %), Sedangkan yang belum tuntas belajar ada 18 siswa atau sebesar (54,55 %) nilai rata rata 62,91 dengan nilai tertinggi 80 dan nilai terendah 45, setelah menggunakan model blended learning aktifitas peserta didik terdapat kenaikan hal ini dapat terlihat dari hasil prestasi,dari yang tuntas 15 peserta didik (45,45%) menjadi 30 peserta didik (90,9,%). Sedangkan yang belum tuntas mengalami penurunan dari 18 peserta didik (54,56%) menjadi 3 peserta didk(09,09%), Tinggi berjumlah5 orang (15,15)%),prestasi cukup berjumlah 10 orang (30,3%),selain itu peserta didik dengan kriteria sangat rendah berjumlah 3peserta didik(09,09%).Berdasarkan data ,peserta didik dengan kirteria prestasi tinggi berjumlah 5 orang (15,15%),predikat cukup berjumlah 10 orang (30,3%),selain itu peserta didik dengan kriteria rendah berjumlah 4 orang (12,12%), dan Peserta didik dengan kriteria sangat rendah berjumlah 3 orang (9,09%),sedangkan untuk kriteria sangat tinggi tidak ada.Setelah dilakukan kegiatan,perolehan nilai peserta didik dengan kriteria prestasi sangat tinggi berjumlah 9 orang (27,27%),prestasi tinggi berjumlah 12 orang (36,36%),cukup berjumlah 9 orang (27,27%),selain itu peserta didik dengan kriteria rendah berjumlah 3 orang(9,09%),dan peserta didik dengan kriteria sangat rendah tidak ada.